The role of Ikaros transcriptional factor in normal hematopoiesis and leukemogenesis: biological and clinical aspects - V. S. Vshivkoo; A. N. Meleshko (Успехи молекулярной онкологии)
Investigation of the pathogenesis and factors effecting recurrence, progression and drug resistance in acute leukemia (AL) remains a major challenge for hematology and other related areas. The role of more than 50 genes and proteins in the AL pathogenesis has been shown, including the well-studied tumor suppressor (CDKN2A/CDKN2B, RB1, PTEN, p53), and classical fusion genes (BCR/ABL1, TEL/AML1, E2A/PBX, MLL translocations). In addition, high frequency of aberrations in genes responsible for lymphoid differentiation have been identified such as transcription factors (PAX5, IKZF1 and EBF1), transcriptional regulation of the genes (ETV6, ERG), and signaling pathways of antigen receptors (BTLA, CD200, TOX, BLNK, VPREB1), as well as genes involved in chemoresistance of leukemia cells (NR3C1). In recent studies, Ikaros abnormalities have been reported to be frequently associated with AL. Ikaros is a member of a Kruppel-like family of zinc finger transcription factors that also includes IKZF2 (Helios), IKZF3 (Aiolos), Eos and Pegasus, and encoded by the IKZF1 gene. In hematopoietic cells Ikaros functions as a transcription factor, a key protein controlling T-, B-, NK-, and dendritic cells early differentiation. At the early hematopoiesis stages, it represses the myeloid and erythroid lineages, and stimulates the lymphoid differentiation. Ikaros also normally modulates immune response and plays role of a tumor suppressor in lymphoid malignances. Data from numerous clinical studies confirmed an association between the presence of IKZF1 aberrations and B-cell and, to a lesser extent, T-cell acute lymphoblastic leukemia (ALL) development. Besides, loss of Ikaros function was associated with progression of myeloproliferative diseases to acute myeloid leukemia (AML) in children. From clinical point of view, particular intragenic IKZF1 deletions and a short (non-functional) protein Ikaros isoforms, which may occur as a result of intragenic deletions or aberrant splicing, are the most significant features. These mutations of IKZF1 gene and Ikaros aberrant expression play a key role in the lymphoid transformation, tumor progression, and may cause development of leukemic cells chemoresistance. Therefore, IKZF1 aberrations should be taken into account as a valuable prognostic marker for risk groups stratification, poor outcome and low survival rare. This review compiles currently available data regarding the frequency and variants of the IKZF1 (Ikaros) aberrations, and the use of them in diagnostics of all types of leukemia and minimal residual disease detection. Although Ikaros has already applied in clinical studies, a growing number of questions  still remain unanswered. Molecular biology of IKZF1 expression and splicing regulation is not well understood. Clinical value of point mutations and subclonal deletion in IKZF1 locus should be elucidated. Prognostic significance of intragenic deletions and aberrant splicing is necessary to clarify for different groups of ALL patients, in connection with other genetic markers and therapy protocol. More detailed clinical analysis required for proving IKZF1 impact on probability of relapse, improving patients, risk stratification and application of minimal residual disease.